2018
DOI: 10.1016/j.joca.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the structural features of osteoarthritis in a year of weight loss

Abstract: In middle-aged persons with mostly mild radiographic OA, structural features changed little over a year and weight loss was not associated with effects on structural changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 20 publications
1
37
0
1
Order By: Relevance
“…The studies assessed structural changes in the joint focusing on different pathologies (Table II). Three studies also looked at changes in clinical symptoms in relation to structural pathologies 22,23,30 . Because the pathologies assessed and OMIs varied markedly, we focused on describing the studies with qualitative synthesis of their results rather than performing a quantitative synthesis.…”
Section: Effect Of Weight Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies assessed structural changes in the joint focusing on different pathologies (Table II). Three studies also looked at changes in clinical symptoms in relation to structural pathologies 22,23,30 . Because the pathologies assessed and OMIs varied markedly, we focused on describing the studies with qualitative synthesis of their results rather than performing a quantitative synthesis.…”
Section: Effect Of Weight Lossmentioning
confidence: 99%
“…Another study 28 based on the OAI found at 96-months follow-up no significant differences in WORMS sum score between groups in the rate of change of global knee cartilage score or cartilage score for each compartment. One study 30 assessed cartilage using the MRI Osteoarthritis Knee Score (MOAKS) 35 and found no significant change between groups.…”
Section: Articular Cartilagementioning
confidence: 99%
“…Another study found that substantial weight loss over 12 months was protective on the biochemical composition of cartilage (dGEMRIC) and reduced cartilage thickness losses 16 . Others did not find differences in bone marrow lesions (BMLs), synovitis and cartilage damage and thickness between subjects with (!20%) and without weight loss 18 . Weight change studies in populations that included only subjects without clinical knee OA at baseline are scarce.…”
Section: Introductionmentioning
confidence: 96%
“…In an earlier study, we assessed cartilage both semiquantitatively and quantitatively in the same study sample and reported no effect of weight loss on this measure over a year, although morphologic changes in cartilage would be unusual in this time frame. BMLs and synovitis have both been shown to change within a few weeks .…”
Section: Discussionmentioning
confidence: 99%